2015
DOI: 10.1016/j.cca.2015.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase plasminogen activator receptor—A valuable biomarker in systemic lupus erythematosus?

Abstract: The expression of uPAR is mainly regulated by growth factors and pro-inflammatory cytokines like basic fibroblast growth factor, epidermal growth factor, tumor necrosis factor, interleukin ( suPAR as a clinical marker of inflammation and organ damagePlasma membrane expression of uPAR as well as the levels of circulating suPAR have been investigated in relation to a broad range of conditions and suPAR has been referred to as a "molecular crystal ball" due to its prognostic value in diseases like tuberculosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 128 publications
0
28
0
Order By: Relevance
“…Obstructive sleep apnoea is associated with heightened systemic inflammation, theoretically contributing to higher uPAR expression [11,[13][14][15]. However, the cleavage of uPAR may be slower in OSA due to decreased levels of uPA [8] and plasmin [5,6,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obstructive sleep apnoea is associated with heightened systemic inflammation, theoretically contributing to higher uPAR expression [11,[13][14][15]. However, the cleavage of uPAR may be slower in OSA due to decreased levels of uPA [8] and plasmin [5,6,23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OSA is associated with decreased levels of transforming growth factor-β [8], an inducer of uPAR transcription [29,30]. These studies suggest that although uPAR expression may be upregulated by systemic inflammation in OSA [11,[13][14][15]; this is counterbalanced by the reduced cleavage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…suPAR is detectable in low, but constant concentrations in the plasma of healthy individuals (2,3). Increased suPAR levels have been observed in numerous pathological conditions including infection (4-6), autoimmune diseases (7,8) and neoplastic diseases (9), as well as during pregnancy (10) and pregnancy-associated disorders (11,12). Preliminary studies indicate that increased plasma suPAR concentrations were observed in patients with non-small-cell lung (13), advanced breast and colorectal (14) and ovarian cancer (15).…”
Section: Introductionmentioning
confidence: 99%